2020
DOI: 10.1007/s12011-020-02460-w
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Folic Acid Supplementation Affects Mineral Status in Female Rats with a Deficiency of These Micronutrients

Abstract: Supplementation with iron and folic acid is widely recommended in women of childbearing age and during pregnancy; however, the effect of such supplementation on mineral status is not well-known. The aim of this study was to determine the effects of oral iron and folic acid, administered together and separately, on copper, zinc, calcium, and magnesium concentrations in the tissues of rats with a deficiency of both these micronutrients. The experiment was performed on 8-week-old female Wistar rats. In the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The metabolism of Fe and Cu is interrelated, and during pregnancy, both a deficiency of Cu and an excess of Fe can affect each other [67]. In women, it has been found that Fe and Cu may competitively interact with each other at the stage of intestinal absorption, and Fe supplementation may decrease Cu levels in the body [68]. It has been observed that in cases of Fe deficiency in the placenta, the level of Cu increases to a higher level than in other tissues [69].…”
Section: The Relationships Between Essential Elementsmentioning
confidence: 99%
“…The metabolism of Fe and Cu is interrelated, and during pregnancy, both a deficiency of Cu and an excess of Fe can affect each other [67]. In women, it has been found that Fe and Cu may competitively interact with each other at the stage of intestinal absorption, and Fe supplementation may decrease Cu levels in the body [68]. It has been observed that in cases of Fe deficiency in the placenta, the level of Cu increases to a higher level than in other tissues [69].…”
Section: The Relationships Between Essential Elementsmentioning
confidence: 99%